Radiation interception, conversion and partitioning efficiency in potato landraces: How far are we from the optimum? - Silva Díaz, C.; Ramírez, D.; Rinza, J.; Ninanya, J.; Loayza, H.; Gómez, R.; Anglin, Noelle L.; Eyzaguirre, R.; Quiróz, R. (MDPI, 2020)
Crop efficiencies associated with intercepted radiation, conversion into biomass and allocation to edible organs are essential for yield improvement strategies that would enhance genetic properties to maximize carbon gain without increasing crop inputs. The production of 20 potato landraces—never studied before—was analyzed for radiation interception ( εi ), conversion ( εc ) and partitioning ( εp ) efficiencies. Additionally, other physiological traits related to senescence delay (normalized difference vegetation index (NDVI) slp ), tuberization precocity ( tu ), photosynthetic performance and dry tuber yield per plant (TY) were also assessed. Vegetation reflectance was remotely acquired and the efficiencies estimated through a process-based model parameterized by a time-series of airborne imageries. The combination of εi and εc , closely associated with an early tuber maturity and a NDVI slp explained 39% of the variability grouping the most productive genotypes. TY was closely correlated to senescence delay (r Pearson = 0.74), indicating the usefulness of remote sensing methods for potato yield diversity characterization. About 89% of TY was explained by the first three principal components, associated mainly to tu , εc and εi , respectively. When comparing potato with other major crops, its εp is very close to the theoretical maximum. These findings suggest that there is room for improving εi and εc to enhance potato production.